Visiting immigration detention : care and cruelty in Australia's asylum seeker prisons - Peterie, Michelle (Global migration and social change., 2022)
This study of immigration detention policy in Australia presents first-hand accounts of more than 70 people visiting and supporting asylum seekers. Documenting and theorising their experiences and treatment, it delivers new perspectives on the profound human costs of hardline immigration policy, both in Australia and beyond.